2008
DOI: 10.1179/174329408x293701
|View full text |Cite
|
Sign up to set email alerts
|

Micro-arc formation of ZrO2 ceramic coatings on AZ91D Mg alloy

Abstract: The aim of the work has been to prepare ceramic coatings containing the ZrO 2 phase on a Mg alloy by micro-arc oxidation technique. The phase composition of the coatings was examined with X-ray diffraction. The surface morphology and the elemental distribution of the coatings were studied with scanning electron microscopy and energy dispersive spectroscopy. The corrosion resistance of the coated samples was examined by the accelerated electrochemical method in 3?5%NaCl solution. The coating was found to be com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Titanium [ 177 , 178 , 179 ] and zirconium compounds [ 150 , 180 , 181 , 182 , 183 , 184 ] are being actively researched as additives due to their very high stability and pore-sealing effect [ 177 , 178 , 184 ]. While titanium is typically used in a form of K 2 TiF 6 , various types of zirconium salts have been tested.…”
Section: Effect Of Energy Input and Electrolyte Composition On Coatin...mentioning
confidence: 99%
See 1 more Smart Citation
“…Titanium [ 177 , 178 , 179 ] and zirconium compounds [ 150 , 180 , 181 , 182 , 183 , 184 ] are being actively researched as additives due to their very high stability and pore-sealing effect [ 177 , 178 , 184 ]. While titanium is typically used in a form of K 2 TiF 6 , various types of zirconium salts have been tested.…”
Section: Effect Of Energy Input and Electrolyte Composition On Coatin...mentioning
confidence: 99%
“…The inconvenience of K 2 ZrF 6 is the hydrolysis of Zr 4+ ions at pH > 4.0, which leads to the precipitation of Zr(OH) 4 in the electrolyte and, consequently, non-uniform discharge distribution and low coating quality. This limits the choice of basic components of the electrolytes to those that support relatively low pH, such as NaH 2 PO 4 [ 182 , 183 ], which, in turn, limits the range of coating phase compositions. Some authors have circumvented this by dual- or two-step anodizing ( Figure 13 ), where PEO of magnesium alloy in the acidic electrolytes [ 180 ] is preceded by a short anodic pre-treatment in alkaline electrolyte; this prevents the excessive anodic dissolution of the magnesium alloy and ensures good corrosion protection [ 180 , 181 ].…”
Section: Effect Of Energy Input and Electrolyte Composition On Coatin...mentioning
confidence: 99%
“…It is reported that a bone-like apatite is produced on the surface of zirconium layer, which is responsible for the improved interfacial strength between the bone and the implant. Previously many researchers studied the effect of Zr and ZrO 2 based coating on Mg alloy to adjust the corrosion rate [ 18 , 61 , 64 66 ]. For instance, using cathodic arc deposition process, Xin et al [ 61 ] developed a 1.5 μ m thick Zr–ZrO 2 dual layer on the AZ91 Mg alloy and tested its mechanical and corrosion behaviour in SBF.…”
Section: Surface Treatments For the Control Of Corrosion Ratementioning
confidence: 99%